Shipping Complexity: Parametric Design for Remote Communities - Carlow, Jason (2013)
This paper presents a system for design and construction of a parametrically designed, structural shell for remote communities. It explains how, through the use of various digital software platforms, a single-layer, structural shell is designed and optimized and subsequently how a series of customized joints can be output for direct digital fabrication. As the customization is focused primary in the joints of the structure, standard dimension, locally sourced structural members can be used. By embedding assembly information onto the physical joints, the system has the capacity to simplify the construction of complex shell structures by workers with basic construction skills. Flat-packed joints can be shipped to remote sites without heavy structural members thereby reducing transportation costs and the overall embodied energy. By lowering cost and simplifying construction of large span structures, the project is intend-ed to extend the benefits of digitally driven design to rural, remote or under-privileged communities.